Evaluating financial audit efficiency: The role of artificial intelligence in proactive negligence mitigation - Hidayat, Noosa Umpu; Lindrianasari, Lindrianasari (Edelweiss Applied Science and Technology, 2025)
This study aims to provide empirical findings on the impact of AI implementation in improving audit efficiency, with a focus on fraud detection to reduce negligence in carrying out audit tasks. The focus of this study is to investigate the perceptions of auditors who have incorporated AI into their daily auditing work practices, comparing the quality of financial audits and fraud detection with those who have not utilized AI. The use of AI in auditing introduces a more efficient and proactive method to identify potential risks and errors. The research methodology involves distributing questionnaires to auditors with substantial experience in the audit industry. The questionnaires are designed to identify differences in audit quality and negligence mitigation perceptions between the use and non-use of AI. The findings of this study offer guidance for auditors in optimizing the benefits of AI to improve audit quality.